The modern monetary theory literature seems to have escaped Drumetz/Pfister - William F. Mitchell (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
This paper provides a response to the recently published critique of modern monetary theory (MMT) by Drumetz/Pfister, which is based on a superficial representation of the body of knowledge and follows a familiar script: MMT is about printing money to solve all problems and will cause accelerating inflation, a plethora of unproductive jobs, and a bond-market revolt. The paper demonstrates that if the authors had consulted the published academic literature, they would have realised that many of the assertions they make are simply without foundation.
Keywords: E12; E62; E63; H6; J6; 330; modern monetary theory; MMT; job guarantee; inflation